
 👍 0
 👎 0
posted by Some Random Girl
Respond to this Question
Similar Questions

Maths
Any help on this question is jiskha.com/questions/1788962/QuestionIntegratex1sinasinxfrom0topiMyfirstthoughtwastoapply (Please add www. to the front as I'm not allowed to post URLs)
asked by Ashley on March 22, 2019 
MathematicsIntegration
Question: Prove that [integrate {x*sin2x*sin[π/2*cos x]} dx] /(2xπ) } from (0π) = [ integrate {sin x*cos x*sin[π/2*cos x} dx ] from (0π). My thoughts on the question: We know that integrate f(x) dx from (0a) = integrate
asked by Shenaya on June 8, 2017 
MathematicsIntegration
Question: For any positive integer n,show that integrate.[(sin x)^2n dx ] from o  π/2 = [(2n)!*π]/[(2)^(2n+1)*(n!)^2 ] What I thought: Let I =int.[(sinx)^2n dx] And again I= int.[ (sin(π/2x))^2n dx] = int.[ (cos)^2n dx] 2I=
asked by Shenaya on June 12, 2017 
calculus
1) Integrate Cos^n(x) dx 2) Integrate e^(ax)Sinbx dx 3) Integrate (5xCos3x) dx I Will be happy to critique your thinking on these. 1) Derive a recursive relation. 2) Simplest by replacing sin(bx) by Exp[i b x] and taking imaginary
asked by Febby on April 13, 2007 
TRIG!
Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1  (3/4)sin^2 2x work on one side only! Responses Trig please help!  Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x +
asked by hayden on February 23, 2009 
calculus/Trig
Suppose you wish to express sin(3t) in terms of sint and cost. Apply the sum formula to sin(3t) = sin(t+2t) to obtain an expression that contains sin(2t)=sin(t+t) and cos(2t)=cos(t+t). Apply the sum formulas to those two
asked by John on May 23, 2010 
Calculus
Hello, Could somebody kindly check my answer for the following question? Find the derivative of the following function: h(x)=3e^(sin(x+2)) h'(x)=3'(e^(sin(x+2))+3(e^(sin(x+2))' h'(x)=0(e^(sin(x+2))+3(e^(sin(x+2))(cos(1))
asked by Constantine on August 18, 2015 
tigonometry
expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by b and using that cos(b)= cos(b) sin(b)= sin(b) gives: sin(ab) = sin(a)cos(b)  cos(a)sin(b)
asked by Pablo on November 26, 2006 
Calculus
Consider the function f(x)=sin(1/x) Find a sequence of xvalues that approach 0 such that (1) sin (1/x)=0 {Hint: Use the fact that sin(pi) = sin(2pi)=sin(3pi)=...=sin(npi)=0} (2) sin (1/x)=1 {Hint: Use the fact that sin(npi)/2)=1
asked by George on September 9, 2008 
Calculus
Consider the function f(x)=sin(1/x) Find a sequence of xvalues that approach 0 such that (1) sin (1/x)=0 {Hint: Use the fact that sin(pi) = sin(2pi)=sin(3pi)=...=sin(npi)=0} (2) sin (1/x)=1 {Hint: Use the fact that sin(npi)/2)=1
asked by George on September 9, 2008